Onset of constituent quark number scaling in heavy-ion collisions at RHIC - Aboona, Bassam; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick (Physical review letters, 2025)
Partonic collectivity is one of the necessary signatures for the formation of quark-gluon plasma in high-energy nuclear collisions. Number of constituent quarks (NCQ) scaling has been observed for hadron elliptic flow 𝑣2 in top energy nuclear collisions at the Relativistic Heavy Ion Collider and the LHC, and this has been theoretically suggested as strong evidence for partonic collectivity. In this Letter, a systematic analysis of 𝑣2 of 𝜋±, 𝐾±, 𝐾0𝑆, 𝑝, and Λ in Au+Au collisions at √𝑠NN=3.2, 3.5, 3.9, and 4.5 GeV, with the STAR experiment at the Relativistic Heavy Ion Collider, is presented. NCQ scaling is markedly violated at 3.2 GeV, consistent with a hadronic-interaction dominated equation of state. However, as the collision energy increases, a gradual evolution to NCQ scaling is observed. This beam-energy dependence of 𝑣2 for all hadrons studied provides evidence for the onset of dominant partonic interactions by √𝑠NN=4.5 GeV.
Veröffentlicht: 11. August 2025
*STAR Collaboration: B.E. Aboona, I.M. Deppner, N. Herrmann, Y.H. Leung, Y. Söhngen [und 369 weitere Personen]
Gesehen am 05.01.2026